Phylodynamic analysis revealed that human mobility and vaccination were correlated to the local spread of SARS-CoV-2 in Republic of Korea - Sangyi Lee; Dong-Wook Lee; Jeong-Min Kim; Da-Won Kim; Ji-Yun Kim; Jeong-Ah Kim; Il-Hwan Kim; Jee Eun Rhee; Kyung-duk Min; Sung-il Cho; Eun-Jin Kim; Jung-Hoon Kwon (Emerging Microbes and Infections, 2023)
Following the global emergence of the SARS-CoV-2 Alpha variant of concern (VOC) in 2020, the Delta variant triggered another wave in 2021. The AY.69 lineage, a Delta VOC, was particularly prevalent in Republic of Korea (South Korea) from May 2021 to January 2022, despite the synchronized implementation of vaccination programmes and non-pharmaceutical interventions (NPIs) such as social distancing. In this study, we used phylogeographic analysis combined with a generalized linear model (GLM) to examine the impact of human movement and vaccination on viral transmission. Our findings indicated that transmission primarily originated in South Korea’s metropolitan areas, and a positive correlation was observed between total human mobility (tracked by GPS on mobile phones and estimated through credit card consumption) and viral spread. The phylodynamic analysis further revealed that non-vaccinated individuals were the primary transmitters of the virus during the study period, even though vaccination programmes had commenced three months prior to the AY.69 outbreak. Our study emphasizes the need to focus on controlling SARS-CoV-2 transmission in metropolitan regions and among unvaccinated populations. Furthermore, the positive correlation between mobility data and viral dissemination could contribute to the development of more accurate predictive models for local spread of pandemics.